The NEC and you perfect together : a comprehensive study of the National Electrical Code - Bierals, Gregory P., 1946- (River Publishers, 2021)
This book uses a unique approach of identifying the terms defined in NEC Article 100 and connecting these definitions to the appropriate sections in Chapters 1 through 9, with detailed explanations that will serve to enhance the reader⁰́₉s understanding of this complex subject. This volume contains extensive information on the following: Branch Circuits Feeders Services Overcurrent Protection Grounding Systems and Equipment Bonding Impedance Grounded Systems Separately Derived Systems Functional Grounding Calculating Ground-Fault Currents Motors, Motor Circuits, and Controllers Transformers Health Care Facilities Hazardous (Classified) Locations Information Technology Equipment Emergency Systems Tables and Examples Readership: Anyone involved in the design and installation of the electrical systems in residential, commercial, institutional, and industrial facilities.
Keywords: Electrical engineering -- Safety regulations -- United States.; elektronické knihy; electronic books